Prospects for the development of the knowledge economy of Ukraine as an actor of the "semi-periphery" of Europe - Kazakova, Nadiya; Miroshnyk, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
In the XXI century. the economic development of countries depends on the increasing role of the human factor in reproduction processes, as well as on the ability to generate innovative transformations. Therefore, examining the patterns of formation, distribution and functioning of the people's wealth, it can be argued that together with knowledge, human capital forms a new type of economy - the knowledge economy, which is the highest stage in the development of the post-industrial and innovative economy. The subject of research of the article is the formation of the knowledge economy as a new key factor in the development of national economies. The goal of this work is to analyze the factors of development of the Ukrainian economy as an actor of the "semi-periphery" of Europe. Task is to study the state and development prospects of the semi-periphery of Europe on the example of Ukraine. The article uses general scientific methods: the study of the development of economic processes was carried out on the basis of the method of scientific abstraction, general and partial. The most common scientific methods of cognition during this research: historical and logical method, analysis, synthesis, method of quantitative and qualitative comparisons, statistical method, economic and mathematical modeling. The following results were obtained: the statistical data characterizing the level of economic development of the semi-periphery countries of Europe and the state of Ukraine were systematized and analyzed, the coefficient of intra-industry international specialization was calculated. The systemic factors that have the greatest influence on the functioning and progress of the economy of the semi-periphery countries have been determined. The problems that hinder the development of semi-periphery actors on the example of Ukraine are highlighted and ways to overcome the shortcomings are proposed. Conclusions: it is advisable to use the results of the work in the domestic and foreign economic activity of countries as recommendations for determining the priority direction of development.